Upaya Pencegahan Stunting melalui Penguatan Kapasitas Kader Posyandu dalam Tehnik Komunikasi Antar Pribadi (KAP) dan Pembuatan Media Konseling Berbasis Artificial Intelegence (AI) - Sulistyorini, Etik; Ratnasari, Nimas; Hayu Palupi, Fitria; Lefiyana; Ilham A, Maulana (LPPM Politeknik Piksi Ganesha, 2024)
Interpersonal Communication (IP) is an effective information delivery technique for behavioral and social changes in the community, especially in stunting prevention behavior. The purpose of this activity is to improve the knowledge and skills of cadres in Interpersonal Communication (IP) techniques and the creation of counseling media (leaflets, posters, flipcharts, booklets) as a support in communicating with targets (pregnant women, mothers of toddlers, teenagers, etc.). As well as facilitating effective and fast response communication through the provision of Artificial Intelligence-based counseling media in the form of a Chatbot application. The results of this activity are that 76 Posyandu cadres have participated in IP technique training and the creation of technology-based counseling media, and IP implementation assistance was provided during Posyandu activities, with the results of 93% good knowledge, 7% sufficient, and none lacking knowledge. Cadre skills in implementing IP are 84% good, 16% sufficient, and none lacking. In addition, a communication media in the form of a